The Effects of Destination Image and Perceived Risk on Revisit Intention: A Study in the South Eastern Coast of Sabah, Malaysia - Amran Harun; Amat Obong; Abdul Wahid Mohd Kassim; Jaratin Lily (2018)
This study investigated the effects of destination image and perceived risk on revisit intention in the South Eastern Coast of Sabah, Malaysia. A total of 171 questionnaires were collected from international tourists through a self-administered questionnaire. The result of this study identified that three dimensions of destination image (travel environment, natural attraction, entertainment, and events) had significant effects on revisit intention. However, perceived risk was not important to the tourists’ revisit intention. The findings have implications on the tourism industry, especially for key players such as the tourism board and travel companies. It also serves as a reference to destinations with a similar risk background.